"Case studies" and research design in the formation of competencies for bachelors in the field of "Biotechnology". (November 2020) - Tikhomirova, L I
Abstract: In modern Russian education there is a process of transition to the subject-subject interaction of a teacher and a student in the learning process. Truly innovative pedagogical technologies are initially built on a competency-based approach and are aimed in learning outcomes at the future professional activity of a graduate. The case method is one of the most significant ones for modern higher education. A consistent combination of pedagogical technology of situational analysis and research design based on the principles of contextual training of students in the direction of training "Biotechnology" at the Federal Budgetary Educational Institution of Higher Education "Altai State University" within the framework of academic disciplines allows successful development of professional and universal competencies, as well as realization of personal qualities. The result of the work of the teacher and students is an intellectual product of a biotechnological research project.